The Estimation of Financial Feasibility of the Development of Superior Teak Stand in The Forest Management Unit of Randublatung - Slamet Riyanto (Jurnal Ilmu Kehutanan)
After the success of teak plant breeding research, Perum Perhutani had set material plantation with superior genetic called Jati Plus Perhutani (JPP) to be used in operational scale. Combined with intensively silvicultural treatment, JPP was expected and assumed to be high productivity stand so that the in the short rotation could produce the merchantable volume equal to volume of woods from long rotation teak plantation. Stand development was an investment activity by employing a number of factors of production to generate a number of benefits in the future. Therefore the financial evaluation was required to determine whether the investment could provide commercial profitability to its owner. The main objective of this study was to evaluate financial performance of development of short rotation teak stand (JPP) by using continuous rotation model called Faustmann Formula or Land Expected Value. Estimation of harvested merchantable volume from thinning and final clear cutting used growth and yield model reconstruction developed by Suprijadi (2010). The model was based on the assumption of similarity between growth and yield depicted in normal table of teak (WvW Table 1932) in site class V and growth and yield model of short rotation of teak plantation in Costarica developed by Perez (2005). The result of this study showed that plantation of the JPP was financially feasible to be implemented as indicated in the Land Expected Value of Rp 10.162.656/Ha. Sensitivity analysis also showed that the profitability of development of JPP stand relatively robust against unexpected changes in the future such as decreasing in production and price and increasing in costs. At all scenarios in the sensitivity analysis, the development of JPP stand was still feasible.